The Mutual Influence between Chinese and Indonesian Language Users in Sunlie Thomas Alexander’s Short Story “My Mother is a Mong Kap San Woman” - Inayatillah, Fafi; Aziz, Abdul Muhaiminul (P3M Politeknik Negeri Media Kreatif, 2024)
This article examines how the characters as language users influence one another and what factors enabling or motivating them to do so in Sunlie Thomas Alexander's short story